KEY DRIVERS OF CHATGPT ADOPTION: MANAGERIAL PERSPECTIVE FROM INDONESIAN COMMUNITIES - Whyte, Frances; Dewi, Yuli (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
The swift progression of AI technology and the growing utilization of ChatGPT in Indonesia highlight the necessity of comprehending its integration within many circles. This study aims to examine the factors influencing the intention to use ChatGPT technology, focusing on three key components of the Unified Theory of Acceptance and Use of Technology (UTAUT), such as Performance Expectancy, Effort Expectancy, and Social Influence. Utilizing a quantitative research approach, data were gathered by purposive sampling through an online survey targeting Gen Y and Z in Indonesia. The sample size was established utilizing the G*Power tool to guarantee a rigorous examination. Partial Least Squares (PLS) analysis was utilized to investigate the correlations between the indicated parameters and adoption intentions. The results offer significant insights into the dynamics of technology acceptability in educational and business settings, highlighting the interaction among performance expectancy, effort expectancy, and social influence. These results enhance the scientific finding in technology adoption and guide developers and policymakers in optimizing ChatGPT incorporation within academic and or business environments. The study consequently presents substantial implications for the wider implementation of AI technologies.